IMPLEMENTATION OF COOPERATIVE LEARNING MODELS AND THEIR IMPACT ON SOCIAL STUDIES LEARNING IN ELEMENTARY SCHOOLS - Imron Burhan; Musfirah Musfirah (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
This study presents a literature review on the implementation of cooperative learning models in Social Studies instruction at elementary schools. The research focuses on identifying the impact of various cooperative learning models, including Jigsaw, STAD, TGT, NHT, Make A Match, and Picture and Picture, on students’ academic and social outcomes. Using a qualitative descriptive approach, articles were selected based on inclusion criteria emphasizing the use of cooperative learning to improve cognitive, affective, and psychomotor aspects of student learning. The review reveals that cooperative learning consistently enhances students’ understanding of concepts, critical thinking skills, learning motivation, active participation, and collaboration abilities. The effectiveness of these models is further strengthened when supported by interactive media, such as PowerPoint or visual-based strategies. Findings indicate that cooperative learning not only improves academic achievement but also fosters active, collaborative, and socially competent learners. These results demonstrate that cooperative learning aligns with the objectives of twenty-first-century education by promoting both cognitive and social development in elementary students, offering practical implications for designing more engaging and meaningful Social Studies learning experiences.